EVALUASI PROGRAM KOMUNIKASI PEMASARAN TERPADU LARAS ASRI RESORT & SPA PERIODE 2010-2012 - Hanna Carissa; Sampoerno - (Universitas Kristen Satya Wacana, 2013)
Laras Asri Resort & Spa is a service company in the shape of a 4 star hotel with a resort concept in Salatiga. In competing with other competitors, certainly the hotel management needs to make a communication strategy to sell his services. The strong competition in the climate of Salatiga hotels there are 15 total needed for effective marketing communications strategy in order to achieve the objectives of the Laras Asri Resort & Spa, that is to be the leading luxury hotel and most comfortable in Central Java, with the main products i.e. either rooms or dwelling.During a period of 3 years of the implementation of the integrated marketing communications program, there is a missmatch in the number of consumer acquisition Number of guest and Total guest in outlets, where the gains that have been achieved does not fulfill the purpose of the hotel. It is therefore through a study entitled